Termokimia Making of Android-Based Lab Virtual Learning Media on Thermochemical Topic - Umar Husaini; Cucu Zenab Subarkah; Ferli Septi Irwansyah (Gunung Djati Conference Series, 2022)
The research is motivated by the importance of android-based virtual lab learning media in thermochemical material. The purpose of this study was to describe the appearance of android-based virtual lab learning media on thermochemical material, analyze the results of the validation test, and the feasibility of the media. The research method is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The virtual lab display consists of eight main menus, namely pretest, theoretical basis, MSDS (Material Safety Data Sheet), procedures, practicum, posttest, compilers and basic competencies. The virtual lab presents thermochemistry practicums related to everyday life which are equipped with animations, pictures and questions. Then the user must fill in the pretest to find out the initial understanding, follow a series of practicums and fill out the posttest to find out their understanding. Research data information can be seen in the compiler menu. The results of the validation test were obtained with an average value of 89.32%. The results of the feasibility test obtained an average value of 90.25%. Based on the results of product validation and feasibility tests, this virtual lab is suitable for use in the learning process